Study over the english model approach to reduce inequality and shift transfer patterns in football- a comparison with Portuguese first league - Dellepiane, Alberto (2022)
This study aims at understanding if the English business model of the EPL help reduce inequality and shift transfers patterns in football. The research has focused on comparing two leagues, first the English Premier League as a model and second to the Primeira Liga Portuguese as a comparison. Therefore, a case study method has been used to present all the events and the connected impacts that helped reduce inequality in English football. The analyzed data has revealed that the English business approach to the management of the football league has brought significant results in increasing competition. In contrast, in the Portuguese first league remains a high discrepancy between top clubs and the others.